A STUDY ON PROVISION OG PUBLIC GREEN OPEN SPACES IN EFFORTS OF IMPROVEMENT AND MANAGEMENT (CASE STUDY: LANGSA CITY) - Reany Syahputri, Rully
One of the policies that favor the interests of the environment is Law No. 26 of 2007 on Spatial Planning which contains provisions regarding the provision of Green Open Space (RTH). Spatial planning for the city area must include a plan for the provision and use of green open space which is at least 30% of the city area. RTH in urban areas consists of public green open space and private green open space where the proportion of green open space in urban areas is at least 30% which consists of 20% public green open space and 10% consists of private green open space. This provision is also contained in the Minister of Public Works No. 5 of 2008 concerning Guidelines for Provision and Utilization of Green Open Space in Urban Areas. However, the facts on the ground state that the existence of green open space is far from ideal proportions, the dominant market forces change the function of the land so that the existence of green open space is increasingly marginalized and even neglected its functions and benefits. In addition, the problem of providing public green open space cannot be applied constantly in each area of at least 20% of the city area due to differences in city typology. Therefore, this study aims to examine the aspect of providing public green open space in autonomous urban areas by calculating based on the availability and needs of public green open space based on population, oxygen demand, and water needs with consideration of environmental services from the provision of green open space. The scope of the research is the Langsa City area which is a medium-sized city with autonomous status. This study was conducted because the existing public green open space has not been identified. Another thing is to evaluate the aspects of providing public green open space by comparing the availability to the need for public green open space. This study uses quantitative methods with GIS (Geographical Information System) spatial analysis techniques, analysis of the calculation of the need for public green space and descriptive statistics. The results show that Langsa City with a medium size city is an autonomous city whose current determination of the area of public green open space is less precise. Based on the calculation of the demand for public green open space seen from the area, it produces a very large area requirement compared to the demand of greeniv open space when viewed from the population, oxygen demand, area based on water needs. This is very difficult to achieve, where there is a large difference between the potential availability area and the minimum requirement of 20% of the city area. The results of the analysis show that the extent of the need for public green open space based on population, based on oxygen demand, and based on water needs tends to be more likely to be achieved when viewed from the characteristics of Langsa City, and the potential availability of public green open space in Langsa City is sufficient for the area of public green open space needed to fulfill the portion of green open space in the city.